Implementation of the Four Pillars of Sustainable Tourism Destinations in the Tourism Village of Kampung Keranggan, South Tangerang - Hubner, Ira B.; Pramono, Rudy; Juliana, Juliana; Sitorus, Nova Bernedeta; Lemy, Diena M. (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Tourism must be directed to truly realize capacity, equity, empowerment and sustainability in building communities. Especially in the era of the pandemic, with the new normal, it is hoped that tourism can become one of the pillars of people's lives. Kampung Keranggan, located in South Tangerang, is one of the tourist villages that has been recognized by the Ministry of Tourism and Creative Economy as being in the "Developing" category. This study wants to examine how the implementation of tourism village development in Keranggan Village through the principles of sustainable tourism in accordance with the four pillars in Ministerial Regulation no. 14 of 2016 / Ministerial Regulation No. 9 of 2021, namely management, economic, socio-cultural and environmental sustainability. This study method is descriptive qualitative analysis, with data collection through interviews, field surveys and implementation of focus group discussions. From the study, it is identified that Kampung Keranggan has begun to implement the four pillars of sustainable tourism destinations, although there are still several aspects that need to be improved.